2018
DOI: 10.1002/jhet.3112
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin–triazole Hybrids and Their Biological Activities

Abstract: Hybridization is emerged as a promising strategy in the discovery of new drugs, especially these with complimentary activities and multiple pharmacological targets that are the potential weapons to prevent the drug resistance. Currently, several hybrids are under different stages of clinical trial, and may be introduced into clinical practice to treat various diseases in the near future. Triazoles including 1,2,3‐triazole and 1,2,4‐triazole as well as coumarins occupy an important position in medicinal chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 97 publications
0
50
0
1
Order By: Relevance
“…The general procedure for preparing targets 9a-l. The precursors 5 and 8 were prepared via literature methods [27][28][29][30]. A mixture of isatins 5 (1.0 mmol), 4-methyl-7-(prop-2-ynyloxy)-2H-chromen-2-one 8 (1.0 mmol), and Cu (OAc) 2 (40 mg) in dimethylformamide (20 mL) was stirred for 24 h at room temperature under N 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The general procedure for preparing targets 9a-l. The precursors 5 and 8 were prepared via literature methods [27][28][29][30]. A mixture of isatins 5 (1.0 mmol), 4-methyl-7-(prop-2-ynyloxy)-2H-chromen-2-one 8 (1.0 mmol), and Cu (OAc) 2 (40 mg) in dimethylformamide (20 mL) was stirred for 24 h at room temperature under N 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The precursors 4 and 6 were prepared via literature methods . A mixture of isatins 4 (1.0 mmol), coumarin 6 (1.0 mmol), and K 2 CO 3 (3.0 mmol) in DMF (20 mL) was stirred at room temperature overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Hybridization of different pharmacophores into a single molecule may provide new candidates with complimentary activities and/or multiple pharmacological targets and/or one part can counterbalance the side effects caused by another part, so hybridization is emerged as an encouraging strategy in the discovery of new drugs with potential therapeutic application . Recently, many isatin–1,2,3‐triazole–coumarin hybrids were found to possess promising anticancer potential and have been widely studied . The structure–activity relationship (SAR) revealed that for these hybrids, the linker between isatin and 1,2,3‐triazole has great influence on the activity .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many isatin–1,2,3‐triazole–coumarin hybrids were found to possess promising anticancer potential and have been widely studied . The structure–activity relationship (SAR) revealed that for these hybrids, the linker between isatin and 1,2,3‐triazole has great influence on the activity .…”
Section: Introductionmentioning
confidence: 99%